Blockchain in Healthcare: Overview of Applications, Challenges, and Future Directions - Wilson, Sareena; Sinha, Vishal Kumar; Malik, Sushma; Rana, Anamika (Journal of Graphic Era University, 2024)
There are numerous healthcare issues which show the potential of blockchain technology such as transparency, interoperability and security of data. Through this study, it tries to offer a very deep explanation of where the Blockchain applications today stand for in the healthcare domain emphasising on possible benefits from the technology and some known challenges that are being faced while actuating those. We then use blockchain applications in the above-mentioned aspects to explain different aspects of use of Blockchain in healthcare like supply chain management, clinical trials, secure medical data exchange and patient empowerment. We also talk about Blockchain from implementation point of view – smart contracts, consensus methods and data privacy. In this publication, we determine whether deploying Blockchain in healthcare raises ethical and legal issues and how existing issues can be addressed. In conclusion, we describe future directions for research and opportunities to use Blockchain to improve healthcare delivery and outcomes.